2014
DOI: 10.1002/chem.201404970
|View full text |Cite
|
Sign up to set email alerts
|

Anionic CH⋅⋅⋅XHydrogen Bonds: Origin of Their Strength, Geometry, and Other Properties

Abstract: CF3H as a proton donor was paired with a variety of anions, and its properties were assessed by MP2/aug-cc-pVDZ calculations. The binding energy of monoanions halide, NO3(-), formate, acetate, HSO4(-), and H2PO4(-) lie in the 12-17 kcal mol(-1) range, although F(-) is more strongly bound, by 26 kcal mol(-1). Dianions SO4(2-) and HPO4(2-) are bound by 27 kcal mol(-1), and trianion PO4(3-) by 45 kcal mol(-1). When two O atoms are available on the anion, the CH⋅⋅⋅O(-) H-bond (HB) is usually bifurcated, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…In an effort to comprehend this behavior, the redshift in the acetylenic C−H stretching frequencies were plotted against other components of the SAPT2 interaction energy, such as induction, dispersion, and exchange repulsion, and the results are presented in Figure A–C. Similar correlations between various energy components for a variety of hydrogen‐bonded systems have been reported in the literature . It can be seen from Figure that the frequency shifts are linearly correlated with induction energy, which is a second‐order electrostatic effect.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In an effort to comprehend this behavior, the redshift in the acetylenic C−H stretching frequencies were plotted against other components of the SAPT2 interaction energy, such as induction, dispersion, and exchange repulsion, and the results are presented in Figure A–C. Similar correlations between various energy components for a variety of hydrogen‐bonded systems have been reported in the literature . It can be seen from Figure that the frequency shifts are linearly correlated with induction energy, which is a second‐order electrostatic effect.…”
Section: Resultssupporting
confidence: 65%
“…Similar correlations between various energy componentsfor avariety of hydrogen-bondeds ystems have been reported in the literature. [45][46][47][48][49][50] It can be seen from Figure 7t hat the frequency shifts are linearly correlated with induction energy,w hich is as econd-order electrostatic effect. The linear correlation suggestst hat even second-order electrostatic effects can influence the vibrational frequency shift.…”
Section: Resultsmentioning
confidence: 99%
“…The first three components are attractive whereas the last is repulsive. A recent study found the attractive interactions between a small C−H hydrogen‐bond donor, trifluoromethane (CF 3 H), and a range of anions in the gas phase were dominated by electrostatic interactions, reinforcing the conventional wisdom of the importance of electrostatic interactions to anion binding.…”
Section: Introductionmentioning
confidence: 93%
“…Nontraditional CÀ H⋯X (X = O, N, π, and anions) hydrogen bonds [1][2][3][4][5][6][7][8] have received much attention because of the presence in many important biological molecules, such as proteins, nucleic acids and nicotinamide adenine dinucleotide (NAD + ). [9] To date, it is known that CÀ H⋯X hydrogen bonding plays an essential role in proteins and nucleic acids, including protein folding, secondary structure determination and stabilization, enzyme catalysis, and nucleic acid recognition.…”
Section: Introductionmentioning
confidence: 99%